Relationship between Socioeconomic Factors and Incidence of Cosmetic Surgery in Tehran, Iran - Mohammad BIDKHORI; Mehdi YASERI; Ali AKBARI SARI; Reza MAJDZADEH (Tehran University of Medical Sciences, 2021)
Background: Cosmetic surgery accompanied with high economic cost is increasing in Iran. It is necessary to be aware about factors affecting cosmetic surgery in order to control its increasing trend. Therefore, we aimed to determine the factors affecting the incidence of cosmetic surgery in Tehran, Iran. Methods: This survey was conducted on 2002 subjects between the ages of 15 to 60 yr using random digit dialing in Tehran, Iran 2015. Demographic data was collected from all of participants and in the presence of cosmetic surgery, the related cosmetic questions were asked in details. Cosmetic surgery was considered as an event and the incidence rate ratio for variables were estimated. For univariate analysis, Poisson regression was used as well as multi-level Poisson regression was used for multivariate analysis. Results: Totally, 224 participants (11%) undergone cosmetic surgery. There was a significant relationship between the age at surgery of participants with the incidence of cosmetic surgery (P<0.001). Cosmetic surgery in women was 1.9 times greater than in men (P <0.001). Incidence Rate Ratio (IRR) for the average and wealthy economic status in comparison to poor level was estimated (IRR=5.6, CI%95: 3.64,8.63) and (IRR=3.14, CI%95: 1.93,5.11), respectively.  In addition, according to multivariate analysis all variables except the level of education and occupation, had significant relationship with the incidence of cosmetic surgery (P<0.001). Conclusion: Cosmetic surgery was related to socioeconomic and demographic factors. Given the high economic burden of this unnecessary surgery, it can be effective to emphasize on awareness-raising programs for those are more likely to undergo cosmetic surgery.